Consumer profile of food delivery apps in the city of Marabá-PA (Research, Society and Development, 2022)
Recently, the use of delivery services increased, becoming something constant in society, mainly during the covid-19 pandemic, due to isolation and the restriction of some activities. In view of the importance of behavior and perspective for digital platforms, this article studies the behavior of consumer expectation in relation to delivery from the municipality of Marabá-PA. This is a descriptive research not qualifying 122 people interviewed will answer an online questionnaire with 16 dated questions. The results were analyzed using electronic templates prepared in Excel from Microsoft 2010. Among the main results obtained, the positive viability in relation to the consumer choosing the quality of two foods as the main criterion stands out. Establishments, as well as a high index of people that disregard the hygienic-sanitary conditions of two establishments, in this way note the importance of two applications to verify the restaurants before including the platform, so that it can transmit reliability to the consumer.